The Psychological Nature of Generalizations - G.G. Kravtsov; O.G. Kravtsov (Культурно-историческая психология, 2023)
The article analyzes the fundamental problem, known in philosophy as the problem of universals, and in psychology as the problem of the essence and types of generalizations. The authors point to the internal inconsistency and lack of persuasiveness of the traditional interpretation of the nature of generalizations proposed by Aristotle. All modern psychology, as indicated in the article, remains a prisoner of the empirical way of generating the general, imposed by the Stagirite. The authors see ways to solve the problem of generalizations in the paradoxical formula proposed by L.S. Vygotsky, who argued that generalization and communication are two sides of the same time. According to this formula, as we communicate, so we generalize, and vice versa. Guided by the most important principle of the cultural-historical approach - the principle of historicism, the authors consider the origin and essence of generalizations in ontogeny. The article highlights and discusses six types of sequentially emerging generalizations. The very first generalization that appears in young children, which can be called primary, sheds light on the inner nature and essence of generalizations, which are a folded program of actions to achieve the goal generated by the child. The next type and level of generalizations can be named after L.S. Vygotsky, worldly concepts and ideas. They differ significantly from the empirical generalizations imposed on children by existing educational methods and programs. According to the authors, the child's mastery of certain levels and types of generalizations is a natural process of development of the psyche and consciousness. At the turn of preschool and primary school age, children develop theoretical thinking with a predominant focus on the mode of action; in the middle grades, they master functional generalizations and a functional style of thinking. In older adolescence and youthful age, opportunities open up for them to familiarize themselves with the scientific and philosophical level of thinking, thanks to the scientific and philosophical types of generalizations. The development of generalizations in the cultural-historical theory is an internal, and, therefore, an essential characteristic of the development of human consciousness.